Variation in Seedling Germinationand Growth in Five Populations Ofvitellariaparadoxa C.F. Gaertn.subsp. Nilotica: A Threatenedusefulfruit Tree Species in Uganda - Odoi, J.B.; Odong, Thomas L.; Okia, C.A.; Okullo, J.L.; Okao, M.; Kabasindi, H.; Muchugi, A.; Gwali, S. (Research Square Platform LLC, 2020)
We studied seedlings germination and growth performance in an economically and socially important fruit tree species of Vitellaria paradoxaC.F. Gaertn.subsp. nilotica (Kotschy) in Uganda. The study aimed at determining variability in germination of the five shea tree seed lots and seedlings growth performance based on their growth traits. Five populations were considered from four agroecological zones of Uganda and 180 candidates plus trees (16 ethnovarieties) selected as seed trees based on their traits for faster growth and high oil yield. A total of 1204 biological seeds were collected and sown in a general tree nursery at Ngetta Zonal Agricultural Research and Development Institute (NgeZARDI)during the month of June 2018 in a randomized incomplete block design with three replications. Significant variation (χ = 526; p < 0.01) was observed in seedling phenotypic traits within and between populations. Regression equation for height growth and leaf size index were given asy = 0.3787 + 12.671x and y = 0.6483 + 15.413x respectively. Root collar diameter was more correlated to leaf size index (0.425) than to height growth (0.30). Clustering of shea tree seedlings based on phenotypic growth traits revealed one aggregated cluster indicating that most of the seedlings from the five populations were similar (Jaccard index 0.92, p < 0.01). However, clustering based on SNP markers revealed three different populations. We recorded higher growth (χ = 708; p< 0.001) in Arua shea population (19.69 cm)compared to the population average (19.04 cm). Red seeded; thin pulped and hairy fruited shea tree ethnovarieties assumed faster growth than the rest. The phenotypic analysis of shea tree seedlings revealed some fast-growing genotypes from the five studied populations. Thesegenotypes can be selected for faster growth for shea tree breeding in Uganda.